Inverse Scattering Problem on the Axis for the Schrödinger Operator with Triangular 2 x 2 Matrix Potential. II. Addition of the Discrete Spectrum - Zubkova, E. I.; Rofe-Beketov, F. S. (Журнал математичної фізики, аналізу, геометрії, 2007)
The theorem of the necessary and sufficient conditions for the solvabilityof ISP under consideration is proved. The method of addition of the discretespectrum to the considered matrix not self-adjoint case is developed. Mathematics Subject Classification: 47A40, 81U40.